HADIS-HADIS POLIGAMI (Aplikasi Metode Pemahaman Hadis Muhammad al-Ghazali) - Masiyan M Syam; Muhammad Syachrofi (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
Polygamy is a classic social problem that has always been discussed till now. There are three views on this issue: first, allowing absolute polygamy; second, forbid absolute polygamy; and third, allowing polygamy with certain conditions and not prohibiting it in extreme ways. All of these views base their views on the same religious text, QS. Al-Nisa': 3, and several hadiths of Muhammad. However, differences occur due to differences in the way or point of view in exploring the hadiths. Literally, it seems contradictory between one hadith and another. Allow and prohibit. Therefore, in this paper, I will read these hadiths in the perspective of Muhammad al-Ghazali. His method in understanding the text of hadith is by examining the hadith with the Qur'an, other hadiths, historical facts, and scientific truths. These hadiths are actually not contradictory but must be understood by referring to QS. Al-Nisa’: 3 earlier. Because according to al-Ghazali, the Qur'an is the most important authoritative source. Therefore, to understand the hadiths of the Prophet must be guided by the Qur'an. In this case, QS. Al-Nisa': 3 allows polygamy but with very strict conditions, namely being just, and other conditions also found in the hadith.